2008
DOI: 10.7150/ijbs.4.23
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic Measurement of Continuity in the Sleep of Fetuses during the Last Week of Pregnancy and in Newborns

Abstract: Our aim was to measure the correlation between fetal electrocardiographic (FECG) recordings of low-risk pregnancies and polysomnographic (PSG) study parameters in low-risk infants born at term as a measurement of perinatal sleep-development continuity. We designed a short, prospective, observational follow-up of physiologic parameters between fetuses and newborns. We studied 10 fetuses from low-risk pregnant female out-patients and the same subjects as low-risk newborns delivered at term. Fetal state (FS) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…1 One study carried out in our laboratory suggested a high correlation of fetal sleep with those sleep measurements developed after birth in neonates. 2 After birth serial recording of several physiologic functions during sleep or polysomnography (PSG) can be obtained by continuous monitoring of electroencephalographic (EEG) signal; eye movements (EOG); electromyographic (EMG) signal of axial and limb muscles; electrocardiographic (EKG) recording; different measurements of respiratory function, such as those obtained by a nasal thermistor, chest and abdominal movements; blood concentrations of oxygen and carbon dioxide sensors are placed in neonates in order to study the organization of the functional state. 3 Preterm infants born at 24 weeks of gestational age (GA) show predominant cyclic rudimentary sleep functional state called Transitional or Indeterminate sleep (IS).…”
Section: Development Of Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…1 One study carried out in our laboratory suggested a high correlation of fetal sleep with those sleep measurements developed after birth in neonates. 2 After birth serial recording of several physiologic functions during sleep or polysomnography (PSG) can be obtained by continuous monitoring of electroencephalographic (EEG) signal; eye movements (EOG); electromyographic (EMG) signal of axial and limb muscles; electrocardiographic (EKG) recording; different measurements of respiratory function, such as those obtained by a nasal thermistor, chest and abdominal movements; blood concentrations of oxygen and carbon dioxide sensors are placed in neonates in order to study the organization of the functional state. 3 Preterm infants born at 24 weeks of gestational age (GA) show predominant cyclic rudimentary sleep functional state called Transitional or Indeterminate sleep (IS).…”
Section: Development Of Sleepmentioning
confidence: 99%
“…5 There is a relative continuity of sleep state from intrauterine through neonatal age, from last weeks of pregnancy to 44 weeks of CA. Such physiologic continuity may reflect the need for sleep state homeostasis of both the fetus and newborn during the transition from intrauterine to extra-uterine environments, 2 requiring approximately one postnatal month of brain development before infant sleep patterns emerge. These physiologic interrelationships defining neonatal state, persist to 4-6 weeks of postnatal life after which infant sleep patterns subsequently emerge to eventually resemble those of adult sleep rhythms by between the first and second years of life.…”
Section: Development Of Sleepmentioning
confidence: 99%
“…However, a proportion of sleep time could not be precisely attributable to either of these sleep patterns rather is accordingly classified as indeterminate. Furthermore, those of newborn spend as much as 75% of total sleep time a day in active sleep (Poblano, Haro, & Arteaga, 2008;Sadeh, Dark, & Vohr, 1996). The proportion of active sleep gradually falls over the first few months after birth to around 25% of total sleep time that approaches to adult proportion.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound provides only the images but does not confirm that the foetus is alive or dead, especially as the foetus sometimes fall asleep for long periods (A. Poblano et al, 2008). Furthermore, ultrasound techniques require a trained technician/physician, frequent repositioning of the transducer and cannot be done in a home environment -something beneficial for problem pregnancies.…”
Section: Introductionmentioning
confidence: 99%